New Single-Layered Paper-Based Microfluidic Devices for the Analysis of Nitrite and Glucose Built via Deposition of Adhesive Tape - Peng Yu; Muhan Deng; Yi Yang (Sensors, 2019)
A simple, low-cost technique has been developed for the rapid fabrication of single-layered paper-based microfluidic devices (μPADs). This technique, for the first time, made use of the deposition of patterned adhesive tape into the filter paper to construct hydrophobic barriers, with the help of toluene. Unlike other reported multi-layered μPADs that merely made use of adhesive tape as a separate layer for sealing or fluid flow controlling, the patterned adhesive tape was simultaneously dissolved and penetrated into the filter paper, which resulted in the successful transfer of the pattern from the tape to the filter paper. To demonstrate the effectiveness of this approach, nitrite and glucose were individually measured; detection limits as low as 0.015 ± 0.004 mM and 0.022 ± 0.006 mM were reported for nitrite and glucose, respectively. Multiplexed analysis of both analytes was also carried out with respective detection limits of 0.048 ± 0.005 mM and 0.025 ± 0.006 mM for nitrite and glucose. The application of the method was demonstrated by measuring nitrite and glucose in spiked artificial urine samples and satisfied recovery results were obtained.